2016
DOI: 10.1103/physrevd.93.064059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modification of gravity on the dynamics of radiating spherical fluids

Abstract: We explore the evolutionary behaviors of compact objects in a modified gravitational theory with the help of structure scalars. Particularly, we consider the spherical geometry coupled with heat and radiation emitting shearing viscous matter configurations. We construct structure scalars by splitting the Riemann tensor orthogonally in f (R, T ) gravity with and without constant R and T constraints, where R is the Ricci scalar and T is the trace of the energy-momentum tensor. We investigate the influence of mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 187 publications
(128 citation statements)
references
References 89 publications
1
127
0
Order By: Relevance
“…For simplicity, we let α = 1, β = 1 and plot ρ eff and ρ eff + p eff which are the function of m and n only, as shown in fig.3. It can be observed from this figure that WEC is also valid for the model (19). Now, we will check the constraints on parameters for the validity of WEC.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity, we let α = 1, β = 1 and plot ρ eff and ρ eff + p eff which are the function of m and n only, as shown in fig.3. It can be observed from this figure that WEC is also valid for the model (19). Now, we will check the constraints on parameters for the validity of WEC.…”
Section: Modelmentioning
confidence: 99%
“…To get an exact solution from the above two inequalities (17) and (18), for the parameters α, β and n, is a quite hard task. In order to achieve this goal, we would consider specific value of α = 0.3 and plot ρ eff and ρ eff + p eff as a function of β and n as shown in fig.1.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cembranos et al [19] studied gravitational collapse in f (R) gravity and found this phenomenon to possibly work as a key tool to constrain modified gravity models that describe late time cosmological acceleration. Yousaf et al [20,21] investigated the irregularity constituents for spherical selfgravitating stars in the presence of an imperfect matter distribution within f (R, T ) gravity and found that the complexity of matter increases with the increase of anisotropic stresses. Yousaf [22] explored collapsing spherical models supporting a vacuum core in a -dominated era within the stellar interior.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti and his coworkers [21] examined the impact of extra Ricci curvature terms on the stability of spherical compact objects filled with anisotropic relativistic matter distributions. Yousaf et al [22] explored the contribution of f (R, T ) extra curvature terms in the outcomes of inhomogeneity factors for dissipative spherical system. They also found factors that causes the maintenance of homogeneous or inhomogeneous matter state, when the system departs hydrostatic equilibrium phase in modified gravity [23].…”
Section: Introductionmentioning
confidence: 99%